2004
DOI: 10.1007/s11072-005-0016-8
|View full text |Cite
|
Sign up to set email alerts
|

Homogenization of the Robin problem in a thick multilevel junction

Abstract: We consider a mixed boundary-value problem for the Poisson equation in a plane two-level junction Ωε that is the union of a domain Ω0 and a large number 2N of thin rods with variable thickness of order ε = O(N −1 ). The thin rods are divided into two levels, depending on their length. In addition, the thin rods from each level are ε-periodically alternated. We investigate the asymptotic behavior of the solution as ε → 0 under the Robin conditions on the boundaries of the thin rods. By using some special extens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2005
2005
2009
2009

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 3 publications
0
12
0
Order By: Relevance
“…In [32], with the help of special extension operators, a convergence theorem was proved for a solution of the Poisson equation in a plane two-level junction with homogeneous Robin boundary conditions at the boundaries of thin rods. In [33], with the Taras Shevchenko National University of Kyiv, Kyiv.…”
Section: Statement Of the Problem And Main Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In [32], with the help of special extension operators, a convergence theorem was proved for a solution of the Poisson equation in a plane two-level junction with homogeneous Robin boundary conditions at the boundaries of thin rods. In [33], with the Taras Shevchenko National University of Kyiv, Kyiv.…”
Section: Statement Of the Problem And Main Resultsmentioning
confidence: 99%
“…This fact was noted in [38] in the course of the homogenization of elliptic equations that describe processes in strongly inhomogeneous thin perforated domains with rapidly varying thickness. If Dirichlet conditions are replaced by Neumann conditions or Fourier conditions, then, as shown in [32], the boundary-value problem does not decompose and consists, in fact, of three boundary-value problems joined together into a single problem by certain conjugation conditions in the junction zone.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that, due to the homogeneous Dirichlet boundary conditions on the vertical sides of the rods from the first level, the original boundary-value problem (1) decomposes in the limit into the two independent problems (13) and (14). Due to the inhomogeneous Neumann boundary conditions on the vertical sides of the rods from the second level, we have obtained the corresponding term on the right-hand side of the ordinary differential equation of problem (14).…”
Section: Discussionmentioning
confidence: 99%
“…These thick junctions have a more complex structure, and, for this reason, the asymptotic investigation has its own specific features and new qualitative results (see [13][14][15][16][17][18]). Here we construct an asymptotic approximation for a solution of a mixed boundary-value problem in a thick two-level junction and investigate the influence of the varying type of boundary conditions on the asymptotic behavior.…”
Section: Introduction and Statement Of The Problemmentioning
confidence: 99%